1979
DOI: 10.1139/b79-095
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sulfur dioxide upon the metabolic level of adenosine triphosphate

Abstract: The ATP content of lodgepole – jack pine (Pinus contorta × banksiana) hybrids in the cordillerean–boreal transition zone was monitored during sulfur dioxide fumigations. Foliage was stabilized for analysis during the course of sulfur dioxide fumigations originating from a sour gas processing plant located in west-central Alberta. Controlled sulfur dioxide fumigations of seedlings were conducted in the laboratory to measure their effect upon ATP content. Field studies demonstrated that ATP concentrations of nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1981
1981
1990
1990

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Thus, light emission was related to ATP content only. In field trials with a variety of different plants, ATP contents are known to correlate with amounts of pollution (Harvey & Legge, 1979). Similar trends were observed in this study.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, light emission was related to ATP content only. In field trials with a variety of different plants, ATP contents are known to correlate with amounts of pollution (Harvey & Legge, 1979). Similar trends were observed in this study.…”
Section: Resultssupporting
confidence: 88%
“…The effect of SO2 fumigations on ATP concentration and energy charge have been studied in higher plants (Harvey & Legge, 1979). Treatments with 1 mol m"3 NaHSOg solutions brought about reduction in the ATP content in lower vascular plants (Aulio, 1984); at 5 mol m"^ it was detrimental to the energy metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…It has earlier been suggested that the inhibitory effect of SO2 might be connected with an impared phosphorylation (Sij and Swanson 1974). The ATP content of Lodgepole-jack pine (Pinus contorta x P. banksiana) hybrids has been shown to decrease linearily with an increase in SO2 concentration (Harvey and Legge 1979). An effect of SO2 on ATP production and ATP content might alter metabolic pathways leading to synthesis and/or degradation of maeromolecules in the chloroplast.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term depolarization of transmembrane PD could result from a direct effect on the ATPase proton pumping and/or a disturbance of the pathways providing ATP. Actually, SO2 or its derivates can reduce ATP production by inhibiting oxidative phosphorylation (Ballantyne 1973, Silvius et al 1975, Harvey and Legge 1979. However, inhibition of sucrose uptake by sulfite is not only due to its effect on the transmembrane PD, because after treatments for 6 or 12 h, 0.1 mM Na^SOj had little effect on the PD although it inhibited sucrose uptake by 40%.…”
Section: Najsomentioning
confidence: 99%